1990
DOI: 10.1163/156853890x00203
|View full text |Cite
|
Sign up to set email alerts
|

Vipera albizona, a new mountain viper from central Turkey, with comments on isolating effects of the Anatolian "Diagonal"

Abstract: The Anatolian "Diagonal" divides Turkish Anatolia into two major zoo- and phytogeographical regions. Along this "Diagonal" a series of closely related species of vipers are distributed: Vipera bornmuelleri, Vipera bulgardaghica, and Vipera wagneri. To this series a new species, Vipera albazona sp. n. is added. The importance of this "Diagonal" as a mechanism for dispersal and speciation is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…This void may have left space for (or may have in part been caused by) the invasion and further differentiation of V. ammodytes in the area. Moreover, a third species is distributed in western Turkey and in particular west of the Anatolian Diagonal reaching Eastern Greece: Montivipera xanthina [44]. The authors suggest a vicariant differentiation of Montivipera beginning in the early Plioecene to the widespread M. xanthina and four more species with restricted distributions along the mountains forming the Anatolian diagonal.…”
Section: The Datamentioning
confidence: 90%
See 1 more Smart Citation
“…This void may have left space for (or may have in part been caused by) the invasion and further differentiation of V. ammodytes in the area. Moreover, a third species is distributed in western Turkey and in particular west of the Anatolian Diagonal reaching Eastern Greece: Montivipera xanthina [44]. The authors suggest a vicariant differentiation of Montivipera beginning in the early Plioecene to the widespread M. xanthina and four more species with restricted distributions along the mountains forming the Anatolian diagonal.…”
Section: The Datamentioning
confidence: 90%
“…Macrovipera is currently considered to contain two species: M. schweizeri and M. lebetina. These have split during the Messinian crisis ca 5MYA [40,43], leaving today a restricted population on the Aegean island group of Milos (M. schweizeri) and M. lebetina with a wide distribution to the east of the Anatolian Diagonal [44] in Turkey, with a wide gap void of the genus in Greek islands and western Turkey (Figure 10). This void may have left space for (or may have in part been caused by) the invasion and further differentiation of V. ammodytes in the area.…”
Section: The Datamentioning
confidence: 99%
“…data stored in our database), have sampled M. wagneri on numerous south-facing slopes. Nilson, Andrén & Flärdh, 1990 Material: ZMADYU 2013/90, 1 ♀, Sarıçiçek Plateau, Kemaliye, province Erzincan, 1790 m a.s.l., 1.vi.2013, leg. Ş. Gültekin, who also provided photographs of three more specimens from the same area (one on www.turkherptil.org and one depicting a couple, pers.…”
Section: Resultsmentioning
confidence: 99%
“…M. albizona is an endemic Turkish mountain viper, which was first described from the Kulmaç Mountains (province Sivas, central Anatolia). Published records indicate that its distribution appears to relate to the Anatolian Diagonal as far east as Yama Mountain, Sivas province ( Figure 2, Nilson et al, 1990;Mulder, 1994;Mallow et al, 2003;Göçmen et al, 2009, Tok et al, 2009). Our M. albizona record from near Kemaliye extends the eastern limit by ca.…”
Section: Montivipera Albizonamentioning
confidence: 99%
“…Şekercioğlu et al (2011) reported that Turkey has 4 major mountain belts, including the Yıldız Mountains in the European part of Turkey; the Taurus Mountains, covering southern Anatolia between the Mediterranean coast and eastern Anatolia; the Köroğlu and Kaçkar Mountains in the Northern Anatolian Mountains; and the Anatolian Diagonal, running from the northeast to the Mediterranean. The Anatolian Diagonal, especially, is a barrier for terrestrial species because it has served as a dispersal corridor for many animals from northeastern to southern Anatolia (Nilson et al, 1990).…”
Section: Introductionmentioning
confidence: 99%